A novel extracellular metallopeptidase domain shared by animal host-associated mutualistic and pathogenic microbes. - Sirintra Nakjang; Didier A Ndeh; Anil Wipat; David N Bolam; Robert P Hirt (PLoS ONE)
The mucosal microbiota is recognised as an important factor for our health, with many disease states linked to imbalances in the normal community structure. Hence, there is considerable interest in identifying the molecular basis of human-microbe interactions. In this work we investigated the capacity of microbes to thrive on mucosal surfaces, either as mutualists, commensals or pathogens, using comparative genomics to identify co-occurring molecular traits. We identified a novel domain we named M60-like/PF13402 (new Pfam entry PF13402), which was detected mainly among proteins from animal host mucosa-associated prokaryotic and eukaryotic microbes ranging from mutualists to pathogens. Lateral gene transfers between distantly related microbes explained their shared M60-like/PF13402 domain. The novel domain is characterised by a zinc-metallopeptidase-like motif and is distantly related to known viral enhancin zinc-metallopeptidases. Signal peptides and/or cell surface anchoring features were detected in most microbial M60-like/PF13402 domain-containing proteins, indicating that these proteins target an extracellular substrate. A significant subset of these putative peptidases was further characterised by the presence of associated domains belonging to carbohydrate-binding module family 5/12, 32 and 51 and other glycan-binding domains, suggesting that these novel proteases are targeted to complex glycoproteins such as mucins. An in vitro mucinase assay demonstrated degradation of mammalian mucins by a recombinant form of an M60-like/PF13402-containing protein from the gut mutualist Bacteroides thetaiotaomicron. This study reveals that M60-like domains are peptidases targeting host glycoproteins. These peptidases likely play an important role in successful colonisation of both vertebrate mucosal surfaces and the invertebrate digestive tract by both mutualistic and pathogenic microbes. Moreover, 141 entries across various peptidase families described in the MEROPS database were also identified with carbohydrate-binding modules defining a new functional context for these glycan-binding domains and providing opportunities to engineer proteases targeting specific glycoproteins for both biomedical and industrial applications.